Heterozygous GABAA receptor β3 subunit N110D knock‐in mice have epileptic spasms. Issue 4 (14th February 2023) - Qu, Shimian; Jackson, Laurel G.; Zhou, Chengwen; Shen, DingDing; Shen, Wangzhen; Nwosu, Gerald; Howe, Rachel; Catron, Mackenzie A.; Flamm, Carson; Biven, Marshall; Kang, Jing‐Qiong; Macdonald, Robert L.
Abstract: Objective: Infantile spasms is an epileptic encephalopathy of childhood, and its pathophysiology is largely unknown. We generated a heterozygous knock‐in mouse with the human infantile spasms‐associated de novo mutation GABRB3 (c.A328G, p.N110D) to investigate its molecular mechanisms and to establish the Gabrb3 +/N110D knock‐in mouse as a model of infantile spasms syndrome. Methods: We used electroencephalography (EEG) and video monitoring to characterize seizure types, and a suite of behavioral tests to identify neurological and behavioral impairment in Gabrb3 +/N110D knock‐in mice. Miniature inhibitory postsynaptic currents (mIPSCs) were recorded from layer V/VI pyramidal neurons in somatosensory cortex, and extracellular multi‐unit recordings from the ventral basal nucleus of the thalamus in a horizontal thalamocortical slice were used to assess spontaneous thalamocortical oscillations. Results: The infantile spasms–associated human de novo mutation GABRB3 (c.A328G, p.N110D) caused epileptic spasms early in development and multiple seizure types in adult Gabrb3 +/N110D knock‐in mice. Signs of neurological impairment, anxiety, hyperactivity, social impairment, and deficits in spatial learning and memory were also observed. Gabrb3 +/N110D mice had reduced cortical mIPSCs and increased duration of spontaneous oscillatory firing in the somatosensory thalamocortical circuit. Significance: The Gabrb3 +/N110D knock‐in mouse has epileptic spasms, seizures, and other neurological impairments that are consistent with infantile spasms syndrome in patients. Multiple seizure types and abnormal behaviors indicative of neurological impairment both early and late in development suggest that Gabrb3 +/N110D mice can be used to study the pathophysiology of infantile spasms. Reduced cortical inhibition and increased duration of thalamocortical oscillatory firing suggest perturbations in thalamocortical circuits.